Output-Based Aid in Colombia : Connecting Poor Households to Natural Gas Service - Mandri-Perrott, Cledan (World Bank, Washington, DC, 2012)
Natural gas connections could bring substantial benefits to poor households in Colombia.compared with other fuels typically used for cooking, natural gas is safer, less expensive, and less environmentally damaging. But even though gas is more affordable, connection fees can put the cost of switching to this fuel out of reach for poor families. The situation in Colombia, with families unable to afford connection fees but able to pay monthly gas service bills, is well suited to the one-time use of output measurable outputs. The Global Partnership on Output-Based Aid (GPOBA) subsidy is designed to make each connection economically feasible while still requiring beneficiary families to make a substantial financial contribution. The project serves as a pilot program, demonstrating a model that regional gas distribution companies can replicate throughout Colombia to speed access to piped natural gas for poor households. By transferring performance risks to privately held regional distribution companies, GPOBA's output-based subsidy approach provides incentives for quality work and timely project completion. GPOBA's effort in Colombia is an example of how output-based aid can increase accountability and leverage the strengths of private firms to produce tangible results.